PROGRAM LINIER FUZZY PENUH DENGAN ALGORITMA MULTI OBJECTIVE LINEAR PROGRAMMING MENGGUNAKAN METODE LEVEL SUM - Yosifayza Septiani (Jurnal Matematika, 2016)
1, Bambang Irawanto2, Susilo Hariyanto3Departemen Matematika FSM Universitas DiponegoroJl. Prof. H. Soedarto, S. H. Tembalang Semarang, b_irawanto.yahoo.co.id ABSTRACT. Fully Fuzzy Linear Programming (FFLP) is one form of fuzzy linear program that the decision variables, limiting the mark, the objective function coefficients, the coefficient constraints and right hand side constraints are fuzzy numbers. Fuzzy numbers used in FFLP is triangular fuzzy numbers.Several methods have been developed to solve FFLP one method Kumar. This thesis explores the completion FFLP with multi-objective algorithm linear programming (MOLP) and compared with the method of Kumar. FFLP problem will be transformed into a problem MOLP with triangular fuzzy numbers and then completed Level Sum Method.Keyword :